Neem Coated Urea for Higher Nitrogen Use Efficiency and Sustainable Soil and Crop Productivity in Sugarcane Plant-Ratoon Sequence - Ch S. Rama Lakshmi; T. Sreelatha; A. Sireesha; K.V. Ramanamurthy; M.B.G.S. Kumari; M. Bharathalakshmi (Journal of the Indian Society of Soil Science, 2025)
Field experiment was conducted at Regional Agricultural Research Station, Anakapalle in Anakapalle district of Andhra Pradesh in two subsequent seasons in sugarcane plant-ratoon sequence. Results revealed that significantly higher values of nitrogen use efficiency was observed with neem coated urea over normal urea. Significantly highest nitrogen uptake was recorded with 150% neem coated urea in plant and ratoon crops, respectively. An additional nitrogen uptake of 5 kg ha-1 was observed in neem coated urea than normal urea. There was no depletion of available nitrogen in post harvest soils and that was observed in both plant and ratoon crops in nitrogen treated plots irrespective of source of nitrogen. Available nitrogen status increased with increasing levels of nitrogen. Regarding available phosphorus and potassium, there were no significant differences among different nitrogen levels. Highest juice brix juice sucrose and juice purity were recorded with lower levels of nitrogen i.e 75% and 100% neem coated urea over higher doses of nitrogen i.e 125% and 150% neem coated urea. However, there was no significant difference between neem coated urea and normal urea regarding juice quality. Numerically higher cane and sugar yields were recorded with neem coated urea over normal urea.